Reduced default mode network suppression during a working memory task in remitted major depression. (May 2015) - Bartova, Lucie; Meyer, Bernhard M.; Diers, Kersten; Rabl, Ulrich; Scharinger, Christian; Popovic, Ana; Pail, Gerald; Kalcher, Klaudius; Boubela, Roland N.; Huemer, Julia; Mandorfer, Dominik; Windischberger, Christian; et al.
Abstract: Insufficient default mode network (DMN) suppression was linked to increased rumination in symptomatic Major Depressive Disorder (MDD). Since rumination is known to predict relapse and a more severe course of MDD, we hypothesized that similar DMN alterations might also exist during full remission of MDD (rMDD), a condition known to be associated with increased relapse rates specifically in patients with adolescent onset. Within a cross-sectional functional magnetic resonance imaging study activation and functional connectivity (FC) were investigated in 120 adults comprising 78 drug-free rMDD patients with adolescent- (n = 42) and adult-onset (n = 36) as well as 42 healthy controls (HC), while performing the n -back task. Compared to HC, rMDD patients showed diminished DMN deactivation with strongest differences in the anterior-medial prefrontal cortex (amPFC), which was further linked to increased rumination response style. On a brain systems level, rMDD patients showed an increased FC between the amPFC and the dorsolateral prefrontal cortex, which constitutes a key region of the antagonistic working-memory network. Both whole-brain analyses revealed significant differences between adolescent-onset rMDD patients and HC, while adult-onset rMDD patients showed no significant effects. Results of this study demonstrate that reduced DMN suppression exists even after full recovery of depressive symptoms, which appears to be specifically pronounced in adolescent-onset MDD patients. Our results encourage the investigation of DMN suppression as a putative predictor of relapse in clinical trials, which might eventually lead to important implications for antidepressant maintenance treatment. Highlights: Reduced default mode network suppression persists even after remission of MDD symptoms. Adolescent-onset rMDD patients show stronger alterations likely reflecting the more severe disease course. The anterior-medial prefrontal cortex appears to be the mediator of these brain network changes in rMDD patients. Reduced default mode network suppression is related to increased rumination.